Femtosecond laser induced forward transfer of indium thin films. (March 2014) - Thomas, John; Bernard, Rodney; Thomas, John T.; Alti, Kamlesh; Chidangil, Santhosh; Kumari, Satchi; Khare, Alika; Mathur, Deepak
Abstract: We report utilization of the laser induced forward transfer technique to re-deposit indium thin films onto the accepter substrate using nJ laser pulses from a femtosecond laser oscillator. Keeping the accepter substrate stationary enables dots of Indium to be deposited; in contrast, linear motion of the accepter substrate facilitates deposition of lines of Indium. The effect of laser pulse energy on the deposition process is studied. The effect of translation speed of donor substrate on the laser induced forward transfer pattern is also probed and an upper limit of translation speed is established beyond which smearing is observed to occur.